Path Analysis of Factors Influencing Multiple Intelligences of Malaysian Medical Students: A Multi-Institutional Study - Wong, Rebecca S.Y; Siow, Heng Loke; Kumarasamy, Vinoth; Fadhlullah Suhaimi, Nazrila Shaherah (2024)
The Multiple Intelligences (MI) Theory by Howard Gardner emphasises that individuals have a unique blend of “capabilities” (“intelligences”), differing significantly from the traditional concept of intelligence measured by conventional intelligence quotient (IQ) tests. This cross sectional, multiinstitutional study aimed to compare the MI of medical students from three Malaysian medical schools, investigate the effects of demographic factors on the MI of students with diverse cultural and socio-economic backgrounds, and examine the effects of MI on academic performance. The MI Inventory was used to assess the MI of medical students. Path analysis was carried out using the SmartPLS software version 2.0. Inter-institutional differences in MI were observed among the students. University A students (53.51 ± 21.99) scored significantly higher than University B students (46.70 ± 20.34) in the naturalist domain (p = 0.05). University A students also scored significantly higher(58.35 ± 21.30) than University B (50.26 ± 19.49; p = 0.014) and University C students (46.90 ± 21.58; p = 0.008) in the musical/rhythmic domain. In the verbal/linguistic domain, University A students (47.94 ± 21.06) scored significantly higher than University Cstudents (39.05 ± 19.23; p = 0.05). Path analysis highlighted a statistically significant effect of family income on the musical intelligence (β = 0.220, t = 2.005, p < 0.05), a domain closely related to verbal/linguistic intelligence. Students from all three medical schools consistently achieved the lowest score in the verbal/linguistic domain and the highest score in the intrapersonal intelligence domain. These findings suggest the need for interventions to enhance language proficiency among medical students. Emphasising MI would make medical education more comprehensive, ultimately enhancing learning in their academic pursuit.